2002
DOI: 10.1542/peds.110.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial Effusion and Tamponade in Infants With Central Catheters

Abstract: The pericardial fluid found in CVC-associated PCE is consistent with the infusate. We speculate that there are several mechanisms, ranging from frank perforation that seals spontaneously to CVC tip adhesion to the myocardium with diffusion into the pericardial space. Routine radiography should be performed, and the CVC tip should be readily identifiable. The CVC tip should remain outside the cardiac silhouette but still within the vena cavae (approximately 1 cm outside the cardiac silhouette in premature infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
164
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(179 citation statements)
references
References 29 publications
2
164
1
2
Order By: Relevance
“…UVC=umbilical venous catheter; UAC=umbilical arterial catheter Fig. 3 Echocardiography demonstrating large pericardial effusion (white arrows) on day three associated cardiac tamponade, guidelines have been published aimed at reducing the risk of cardiac perforation [3,4,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UVC=umbilical venous catheter; UAC=umbilical arterial catheter Fig. 3 Echocardiography demonstrating large pericardial effusion (white arrows) on day three associated cardiac tamponade, guidelines have been published aimed at reducing the risk of cardiac perforation [3,4,6].…”
Section: Discussionmentioning
confidence: 99%
“…The transmural diffusion of parenteral nutrition fluids into the pericardial space further contributes to the accumulation of fluid. Contrary to catheter-associated infections and thrombosis, which increase over time, pericardial effusion may occur directly after the insertion of catheters, or later, with a peak at three days following catheter insertion [4]. The malposition of central catheters is considered to be the main risk factor for pericardial effusion, particularly if the catheter tip projects into the right atrium or shows angulation [1,3,8].…”
Section: Discussionmentioning
confidence: 99%
“…In the case series from Nowlen et al, 7 the catheter tip was last reported within the pericardial reflection in 92% of cases (82% within cardiac silhouette and 10% at vena cavae junction with right atrium). In our patient, the catheter tip was last reported at the right atrium-SVC junction.…”
Section: Question: How To Prevent This Complication?mentioning
confidence: 97%
“…Nowlen et al 7 reported the largest case series of central venous catheter-related pericardial effusions in infants to date. In this series of 61 pericardial effusions in infants secondary to central venous catheters, sudden cardiac collapse requiring cardiopulmonary resuscitation was reported in 37 cases (61%).…”
mentioning
confidence: 99%
“…Nadroo et al [7] report three deaths caused by cardiac tamponade out of 390 placements of PICC. Nowlen et al [2] reported 14 cases of pericardial effusion in newborns with deep venous access in six different units of neonatology over 2 years. This author also reported another 47 cases that were in the literature between 1970 and 1999.…”
Section: Fig 1 -Echocardiogram Of Case 1 Showing Severe Pericardial mentioning
confidence: 99%